PENGEMBANGAN SISTEM TRANSPORTASI HIJAU KAMPUS UNIVERSITAS NEGERI SEMARANG SEBAGAI PENDUKUNG MOBILITAS CIVITAS AKADEMIKA - Prihanto, Teguh (Semarang State University, 2014)
Campus environment is an important public place where many people move for a full day. One of the main supporters of the movement of people and goods is an effective and efficient transportation. Internal Transport, Infrastructure and Mobility become important in the framework to determine the performance of an internal transport system and its implementation in the field. Some aspects related to the study include three aspects, namely: (1) internal transport system of governance; (2) internal transportation infrastructure, and (3) the movement of the user. The purpose of this study was to: (1) Develop supporting infrastructure green transportation program; (2) Develop environmental health Unnes optimal campus; (3) Develop a green transportation system that supports mobility Unnes academic community; and (4) Develop a green transportation system that supports the academic community Unnes performance. This study will be conducted by the research design and development (research and development / R and D) with a qualitative approach. This approach makes it very appropriate because it relates to the general purpose of the research: (1) Develop infrastructure supporting green transportation program; (2) Develop environmental health Unnes optimal campus; (3) Develop a green transportation system that supports mobility Unnes academic community; (4) Develop a green transportation system that supports the academic community Unnes performance. Based on the identification of conditions in the field, the internal transport system in Campus Unnes have now been partially implemented in the form of physical elements, namely Campus Unnes internal transport infrastructure, transportation and system settings. Although it has been available, facilities and infrastructure are still not optimal in supporting the movement and the academic community as a user convenience. Comfort academic community and environmental health is also affected by the level of pollutants present in the campus area.Lingkungan kampus merupakan tempat publik yang penting di mana banyak orang beraktivitas selama sehari penuh. Salah satu pendukung utama dari pergerakan manusia dan barang adalah transportasi yang efektif dan efisien. Transportasi Internal, Infrastruktur dan Mobilitas menjadi hal penting dalam kerangka untuk mengetahui kinerja sebuah sistem transportasi internal dan implementasinya di lapangan. Beberapa hal yang terkait dengan kajian meliputi tiga aspek yaitu: (1) sistem tata kelola transportasi internal; (2) sarana prasarana transportasi internal dan (3) pergerakan pengguna. Tujuan dari penelitian ini adalah untuk: (1) Mengembangkan sarana prasarana pendukung program transportasi hijau; (2) Mengembangkan kesehatan lingkungan kampus Unnes yang optimal; (3) Mengembangkan sistem transportasi hijau yang mendukung mobilitas civitas akademika Unnes; dan (4) Mengembangkan sistem transportasi hijau yang mendukung kinerja civitas akademika Unnes. Penelitian ini akan dilaksanakan dengan desain riset dan pengembangan (research and development/ R and D) dengan pendekatan kualitatif. Pendekatan ini dipandang sangat tepat karena berkaitan dengan tujuan umum penelitian yaitu: (1) Mengembangkan sarana prasarana pendukung program transportasi hijau; (2) Mengembangkan kesehatan lingkungan kampus Unnes yang optimal; (3) Mengembangkan sistem transportasi hijau yang mendukung mobilitas civitas akademika Unnes; (4) Mengembangkan sistem transportasi hijau yang mendukung kinerja civitas akademika Unnes. Berdasarkan identifikasi kondisi di lapangan, sistem transportasi internal Kampus Unnes di Sekaran sebagian telah terimplementasi dalam bentuk elemen-elemen fisik, yaitu infrastruktur transportasi internal Kampus Unnes, sarana transportasi dan sistem pengaturannya. Meski telah tersedia, sarana dan infrastruktur masih belum optimal dalam mendukung pergerakan dan kenyamanan civitas akademika sebagai pengguna. Kenyamanan civitas akademika dan kesehatan lingkungan juga dipengaruhi oleh tingkat polutan yang ada dalam kawasan kampus.